Unlocking Student Engagement: Creation, Adaptation, and Application of an Educational Escape Room Across Three Pharmacy Campuses. (April 2020) - Eukel, Heidi; Frenzel, Jeanne; Frazier, Kyle; Miller, Micah
Background. Educational escape rooms are positively received by students, increase knowledge, and serve as a platform for theactive application of teamwork and team-based communication. Aim. This article focuses on detailing an educational escape room that isadaptable and transferable for use with any course or discipline. Methods. Puzzles are created around the educational objectives of the course or unit. Puzzles include ciphers, jumbles, coded messages, combination locks, rebuses, and data hunts. Students work in teams to solve content-specific puzzles to escape a room. Teams which solve all of the puzzles in the allotted time are considered to have successfully escaped the room. Gameplay can range from 60 to 75 minutes. Facultyled debriefing is an important part of the educational innovation. Results and Conclusion. This escape room uses collaborative learning to increasestudent knowledge and skills in educational content. The learning experience is enhanced through dynamic studentengagement with the focused topic. This topic can easily be changed to a different course topic and the corresponding gameplay puzzles adapted and transferred for use with a variety of disciplines. This manuscript details the transferability of the educational escape room to 3 campuses and provides insight for successful implementation.